Maslahah Mursalah's Analysis of Women Small Traders in Meeting Household Needs at Sambas Morning Market, West Kalimantan - Asman, Asman; Aamer, Mohamed (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This research discusses the activities of women as small traders in the Sambas Morning Market and their contribution to the household economy from the perspective of maslahah mursalah. The problem raised is the extent to which the economic role of women small traders contributes to meeting household needs and how these activities are reviewed from the perspective of Islamic law, especially the concept of maslahah mursalah. This study uses a qualitative method with a field approach. Data was collected through in-depth interviews, direct observation, and documentation of the activities of women traders in the market. The results of the study show that women small traders make a significant contribution in supporting basic household needs, such as food, children's education, and health. From the point of view of maslahah mursalah, this activity is classified as a form of benefit that does not contradict the provisions of sharia because it brings real benefits, both individually and socially. As long as this trade activity is carried out by holding Islamic values such as honesty, responsibility, and maintaining ethics and self-respect, the existence of women in the informal economic sector can be accepted and justified within the framework of Islamic law. Abstrak: Penelitian ini membahas aktivitas perempuan sebagai pedagang kecil di Pasar Pagi Sambas dan kontribusinya terhadap ekonomi rumah tangga dalam perspektif maslahah mursalah. Permasalahan yang diangkat adalah sejauh mana peran ekonomi perempuan pedagang kecil berkontribusi dalam memenuhi kebutuhan rumah tangga dan bagaimana aktivitas tersebut ditinjau dari sudut pandang hukum Islam, khususnya konsep maslahah mursalah. Penelitian ini menggunakan metode kualitatif dengan pendekatan lapangan. Data dikumpulkan melalui wawancara mendalam, observasi langsung, dan dokumentasi terhadap aktivitas para pedagang perempuan di pasar tersebut. Hasil penelitian menunjukkan bahwa perempuan pedagang kecil memberikan kontribusi signifikan dalam menopang kebutuhan dasar rumah tangga, seperti pangan, pendidikan anak, dan kesehatan. Dari sudut pandang maslahah mursalah, aktivitas ini tergolong sebagai bentuk kemaslahatan yang tidak bertentangan dengan ketentuan syar’i karena membawa manfaat nyata, baik secara individu maupun sosial. Selama aktivitas perdagangan ini dijalankan dengan memegang nilai-nilai Islam seperti kejujuran, tanggung jawab, serta menjaga etika dan kehormatan diri, maka keberadaan perempuan dalam sektor ekonomi informal ini dapat diterima dan dibenarkan dalam kerangka hukum Islam.